2023
DOI: 10.2106/jbjs.rvw.22.00128
|View full text |Cite
|
Sign up to set email alerts
|

Local Soft-Tissue Thickness vs. Body Mass Index as Predictors of Complications After Total Knee or Hip Arthroplasty

Sarthak Parikh,
Tejbir S. Pannu,
Ty Davis
et al.

Abstract: » Body mass index (BMI) is a nonspecific measure of general fat composition that demonstrates little conclusive or definitive association with surgical site complications after total knee and total hip arthroplasty.» Quantifying soft-tissue thickness (STT) around the joint of interest has shown positive correlations with complications and is arguably a better predictor than BMI.» In this literature review, 14 articles (7 discussing hips and 7 discussing knees) discussing the association of STT, BMI, and surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…Conflicting evidence exists as to whether obesity, represented by an increased BMI, has an impact on implant placement in TKA [5,7,31]. However, given BMI's limitations in describing local fat distribution [9], local soft tissue thickness (LSTT) might be a more appropriate parameter to investigate regarding its impact on complications and implant placement in total joint arthroplasty (TJA) [26]. Following this rationale, several studies examined LSTT in relation to complications after TKA [35,37,39] but only one study reported on the impact of LSTT on implant placement [30].…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting evidence exists as to whether obesity, represented by an increased BMI, has an impact on implant placement in TKA [5,7,31]. However, given BMI's limitations in describing local fat distribution [9], local soft tissue thickness (LSTT) might be a more appropriate parameter to investigate regarding its impact on complications and implant placement in total joint arthroplasty (TJA) [26]. Following this rationale, several studies examined LSTT in relation to complications after TKA [35,37,39] but only one study reported on the impact of LSTT on implant placement [30].…”
Section: Discussionmentioning
confidence: 99%
“…12 Further, surgical site thickness has been shown to be a risk factor for infection, wound complications, and early failure following total knee and hip arthroplasty. 14,25,31 In a retrospective review of 1110 patients undergoing a total hip arthroplasty, Sprowls et al 35 found that the surgical site thickness was predictive of infection and associated with revision surgery (odds ratio: 1.022 [1.004-1.041]; P = .02). They suggest that a radiographic measure accurately captures surgical site adipose compared with BMI and was potentially a modifiable risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, preoperative radiographic soft tissue thickness has been suggested as a predictor of outcomes following hip, knee, and shoulder arthroplasty. 25,26,28,33,36,38,41 In hip arthroplasty, measurements included the distance from the tip of the greater trochanter to the skin along a perpendicular line to the femoral diaphysis, whereas knee arthroplasty focused on prepatellar and pretubercular thickness measurements. 26,36,38 Shoulder arthroplasty measured the deltoid muscle and subcutaneous fat thickness using concentric circles centered on the humeral head.…”
Section: Introductionmentioning
confidence: 99%